Adherence to a Mediterranean diet and risk of diabetes: a systematic review and meta-analysis. Issue 7 (13th August 2014) - Schwingshackl, Lukas; Missbach, Benjamin; König, Jürgen; Hoffmann, Georg
Abstract: Objective: Adherence to a Mediterranean diet is associated with significant improvements in health status. However, to date no systematic review and meta-analysis has summarized the effects of Mediterranean diet adherence on the risk of type 2 diabetes mellitus. Design: Electronic searches for randomized controlled trials and cohort studies were performed in MEDLINE, SCOPUS, EMBASE and the Cochrane Trial Register until 2 April 2014. Pooled effects were calculated by an inverse-variance random-effect meta-analysis using the statistical software Review Manager 5·2 by the Cochrane Collaboration. Setting: Meta-analysis of randomized controlled trials and cohort studies. Subjects: Eligibility criteria: 19+years of age. Results: One randomized controlled trial and eight prospective cohort studies (122 810 subjects) published between 2007 and 2014 were included for meta-analysis. For highest v . lowest adherence to the Mediterranean diet score, the pooled risk ratio was 0·81 (95 % CI 0·73, 0·90, P <0·0001, I 2 =55 %). Sensitivity analysis including only long-term studies confirmed the results of the primary analysis (pooled risk ratio=0·75; 95 % CI 0·68, 0·83, P <0·00001, I 2 =0 %). The Egger regression test provided no evidence of substantial publication bias ( P =0·254). Conclusions: Greater adherence to a Mediterranean diet is associated with a significant reduction in the risk of diabetes (19 %; moderate quality evidence). These results seem to be clinically relevant for public health, in particular for encouraging a Mediterranean-like dietary pattern for primary prevention of type 2 diabetes mellitus.